Topical anaesthetic patches for postoperative wound pain in laparoscopic gynaecological surgery: a prospective, blinded and randomised trial - Berlit, Sebastian; Tuschy, Benjamin; Brade, Joachim; Hornemann, Amadeus; Sütterlin, Marc (Archives of gynecology and obstetrics, 2014)
Purpose: Aim of this prospective study was to investigate the effectiveness of eutectic mixture of local anaesthetic (EMLA®) patches on every abdominal incision for pain relief after gynaecologic laparoscopic surgery. Methods: A total of 121 women were prospectively randomised to receive either placebo (control group) or EMLA® (study group) patches on all abdominal incisions. Postoperative pain was assessed 24 and 48 h after surgery using the short form of the McGill Pain Questionnaire (SF-MPQ). The amount of analgesic pain medication on demand was assessed in both groups. Results: Sixty women were allocated to the study group and 61 patients to the control group before laparoscopic surgery. There were no statistically significant differences regarding age, body mass index (BMI), duration of surgery and blood loss comparing both groups. There were no statistically significant differences between both groups with regard to postoperative total pain scores 24 h (McGill total score: 31.77 ± 27.95 vs. 36.80 ± 31.39, p = 0.3535) and 48 h (McGill total score: 19.18 ± 20.09 vs. 26.61 ± 27.70, p = 0.0942) after surgery. Time to mobilisation after surgery (hours) was significantly shorter in the study group (5.01 ± 3.72 vs. 5.78 ± 3.04, p = 0.0423). Conclusion: Despite of a significant reduction of time for mobilisation transdermal anaesthetic patches after gynaecologic laparoscopic surgery did not lead to decreased postoperative pain scores.